Model Development of Savi–Based E-Module for Arabic Instruction at Islamic Junior High School in Bandar Lampung, Indonesia - Koderi Koderi; Zulfiati Syahrial (Humaniora, 2018)
This research aimed to get data of Arabic instructional processes; develop Somatic, Auditory, Visual, and Intellectual (SAVI)-based e-module for Arabic instruction at Islamic junior high schools (Madrasah Tsanawiayah - MTs); and obtain empirical data of SAVI-based e-module effectiveness to improve students’ achievement in Arabic lesson. Models of Dick and Carey, as well as Hanaffin and Peck, were utilized and modified into four stages. It comprised of preliminary research, model designing and development, validation, evaluation and revision, as well as model effectiveness test implementation. Overall, the expert judgment on validity model was very good including experts in instructional design, instructional content, and instructional media. Generally, the response of students was also very good regarding one to one learner, small group, as well as field trial on acceptance and utility model. The tryout result of effectiveness model shows that the average pretest score is 48,1666, posttest is 75,775, and the difference between those is 25,608. The value of tobserved is also higher than tcritical (15,42807>2,02268). It means that SAVI-based e-module for Arabic instruction at MTs is effective to improve students’ achievement.